Effect of flurbiprofen derivative (SGK597) on cell proliferation and apoptosis of breast cancer cell lines - ORUN, OYA; MEGA TİBER, PINAR (My University, 2022)
Background and Aims: The incidence of breast cancer is increasing day by day, especially in women. The search for new drugs against breast cancer is the focus of attention in research. Breast cancer and prostate cancer have remarkable biological similarities. Therefore, the 4-(4-chlorophenyl)-3-(1-(2-fluoro-[1,1'-biphenyl]-4-yl)ethyl)-5-((4-fluorobenzyl)thio)-4H1,2,4-triazole (SGK597) compound that is suppressing cell proliferation in prostate cancer, was studied in MCF-7 breast cancer and MCF-10A mammary epithelial cell lines. Methods: The WST-8 method was used to determine cell viability and cytotoxicity of SGK597 in MCF-7 and MCF10-A cell lines. The JC-1 test was applied to determine changes in mitochondrial membrane potential. The protein expression levels of Bax, Bcl-2, and c-PARP associated with apoptosis were determined using Western blot analysis. Results: After 24 and 48 hours of incubation of SGK597, the IC50 values were 28.74 μM and 17.28 μM for MCF-7; 65.9 μM and 50.5 μM for MCF-10A, respectively. Mitochondrial membrane potential showed a tendency toward depolarization in MCF-7 cells as a result of increasing concentration of SGK597, while the same tendency was not seen for MCF-10A. As a result of western blot experiments, no increase in the Bax/Bcl-2 ratio and c-PARP expression level was observed, indicating no apoptosis. Conclusion: It was observed that the compound SGK597 suppressed MCF-7 cell proliferation. These results indicate that SGK597 may be a candidate compound for use as an anticancer agent.
Keywords: Apoptosis; breast cancer; flurbiprofen; thioether; triazole